Effects of heavy metals on bioremediation of diesel by Antarctic microalga Tritostichococcus sp. - Goh, Wen Xi; Tae, Ruo-Shan; Lim, Zheng Syuen; Wong, Chiew Yen; Ahmad, Siti Aqlima; Kok, Yih Yih; Convey, Peter (Polish Polar Research, 2024)
Hydrocarbon spillage has long been a concern in Antarctica as it can result in detrimental effects on Antarctic biota and ecosystems. Bioremediation, using microorganisms such as microalgae, represents one of the most effective and least damaging methods developed to remove pollutants from the environment. However, the effectiveness of bioremediation in eliminating diesel can be influenced by co-contamination of the spill area by heavy metal ions, as is often the case. This study assessed the effects of zinc (Zn), lead (Pb), copper (Cu) and cadmium (Cd) on the bioremediation of diesel by a freshwater Antarctic microalga isolated from soil, Tritostichococcus sp. WCY_AQ5_1 (GenBank accession number: OQ225631), under laboratory conditions. Toxicity testing of heavy metals (1 to 16 ppm) on Tritostichococcus sp. showed that microalgal specific growth rates and pigment ratios remained constant up till 8 ppm for all four heavy metals, an implication of toxicity at 16 ppm. In subsequent experiments, where diesel was introduced, sub-lethal Zn and Cd ion concentrations (2 to 10 ppm) did not significantly affect the biodegradation ability of Tritostichococcus sp. In contrast, sub-lethal Pb and Cu levels led to reduced diesel biodegradation at higher concentrations (8 to 10 ppm) by approximately 33% and 55%, respectively. Intriguingly, patterns of microalgal growth were not correlated with those of biodegradation efficiency as a prominent increase in growth of Zn-exposed cultures was observed at 8 and 10 ppm, and growth of Cu-exposed cultures peaked at 6 ppm. On the other hand, microalgal growth in Pb and Cd-exposed cultures (2 to 10 ppm) generally remained the same as control (0 ppm).